FRI0502 Long-Term Safety of Adalimumab Treatment in Pediatric Patients with Polyarticular Juvenile Idiopathic Arthritis and Enthesitis-Related Arthritis. (9th June 2015) - Ruperto, N.; Lovell, D.J.; Kingsbury, D.J.; Burgos-Vargas, R.; Imagawa, T.; Horneff, G.; Quartier, P.; Goodman, S.I.; Reiff, A.; Giannini, E.H.; Cardoso, A.; Anderson, J.K.; et al.
Abstract : Background: The long-term safety of anti-tumor necrosis factor (TNF) drugs is particularly important in pediatric patients (pts) who may require prolonged treatment of their inflammatory disease. Objectives: To evaluate long-term rates of serious adverse events (AE) and anti-TNF AEs of special interest in adalimumab (ADA) clinical trials in pediatric pts with polyarticular or polyarticular course juvenile idiopathic arthritis (pJIA) or enthesitis-related arthritis (ERA). Methods: Safety data from pts treated with ADA, either dosed 24 mg/m 2 BSA every other week (eow) or 20 mg eow (<30 kg) to 40 mg eow (≥30 kg), in 4 clinical trials in pJIA and ERA were analyzed. Three studies in pJIA enrolled pts aged 2–17 years (yrs) treated with ADA for up to 8.5 yrs. One study enrolled pts with ERA aged 6–17 yrs who were treated with ADA for up to 52 wks in this analysis. AEs of special interest included malignancy, serious infections, tuberculosis (TB) and other opportunistic infections, and death. Events per 100 patient-years (PY) were calculated using AEs reported after first ADA dose through 70 days after last dose. Results: ADA was administered to 274 pts, representing 769.0 PY of exposure. Infections, the most common AE, occurred in ≥10% of pts. Serious infection was the most frequently reported SAE (table ). One case of latent TB was reported. No malignancies, opportunistic infections, or deaths were reported. 8.4% of pts (23/274) discontinued study due to AE (range, 5.1% in age <5 yr to 9.6% in ages 5 - <12 yrs). Other than uveitis, liver events, and injection site-related AEs, no differences in AE rates were observed between age groups.(table ) Conclusions: These data provide support for the long-term safety of ADA in pediatric pts aged 2–17 yrs with pJIA or ERA and demonstrate a safety profile consistent with ADA in adult pts and known information about the anti-TNF class. Acknowledgements: AbbVie funded the studies (NCT00048542, NCT00690573, NCT00775437, and NCT01166282 ), contributed to their design and was involved in the collection, analysis, and interpretation of the data, and in the writing, review, and approval of the publication. Medical writing support was provided by Kathleen V. Kastenholz, PharmD, MS, of AbbVie. Disclosure of Interest: N. Ruperto Grant/research support from: AbbVie, AstraZeneca, BMS, Janssen, "Francesco Angelini", GlaxoSmithKline, Italfarmaco, Novartis, Pfizer, Roche, Sanofi Aventis, Schwarz Biosciences, Sobi, Xoma, and Wyeth for the PRINTO network paid to GASLINI Hospital, Consultant for: AbbVie, Amgen, Astellas, Alter, AstraZeneca, Biogen Idec, Boehringer, BMS, CD-Pharma, Celgene, Crescendo Bioscience, EMD Serono, Italfarmaco, Janssen, MedImmune, Medac, Novartis, Novo-Nordisk, Pfizer, Roche, Sanofi Aventis, Servier, Sinergie, Takeda, and Vertex, Speakers bureau: AbbVie, Amgen, Astellas, Alter, AstraZeneca, Biogen Idec, Boehringer, BMS, CD-Pharma, Celgene, Crescendo Bioscience, EMD Serono, Italfarmaco, Janssen, MedImmune, Medac, Novartis, Novo-Nordisk, Pfizer, Roche, Sanofi Aventis, Servier, Sinergie, Takeda, and Vertex, D. Lovell Consultant for: AbbVie, AstraZeneca, Boehringer Ingelheim, Celgene, Centocor, Bristol-Myers Squibb, Genentech, GlaxoSmithKline, Horizon Pharma, Janssen Biologics B.V., Novartis, Pfizer, Regeneron, Hoffman La-Roche, and UBC and served on data and safety monitoring boards for Forest Research, Speakers bureau: Genentech and Wyeth Pharmaceuticals, D. Kingsbury Grant/research support from: AbbVie, R. Burgos-Vargas Grant/research support from: AbbVie, Consultant for: AbbVie, BMS, Janssen, Pfizer, and Roche, Speakers bureau: AbbVie, BMS, Janssen, Pfizer, and Roche, T. Imagawa Grant/research support from: AbbVie/Eisai and Novartis, Consultant for: AbbVie/Eisai, Speakers bureau: AbbVie/Eisai, Chugai, and Mitsubishi Pharma, G. Horneff Grant/research support from: AbbVie, Pfizer, and Roche, Speakers bureau: AbbVie, Novartis, Pfizer, and Roche, P. Quartier Grant/research support from: AbbVie, Novartis, Pfizer, BMS, Chugai-Roche, Medimmune, Servier, and Swedish Orphan Biovitrum, Consultant for: AbbVie, Novartis, Pfizer, BMS, Chugai-Roche, Medimmune, Servier, and Swedish Orphan Biovitrum, S. Goodman Consultant for: Amgen, A. Reiff Consultant for: AbbVie and Amgen, Speakers bureau: AbbVie and Amgen, E. Giannini Consultant for: AbbVie, A. Cardoso Shareholder of: AbbVie, Employee of: AbbVie, J. Anderson Shareholder of: AbbVie, Employee of: AbbVie, N. Varothai Shareholder of: AbbVie, Employee of: AbbVie, J. Kalabic Shareholder of: AbbVie, Employee of: AbbVie, A. Martini Grant/research support from: AbbVie, AstraZeneca, BMS, Janssen, "Francesco Angelini", GlaxoSmithKline, Italfarmaco, Novartis, Pfizer, Roche, Sanofi Aventis, Schwarz Biosciences, Xoma, and Wyeth for the PRINTO network paid to GASLINI Hospital, Consultant for: AbbVie, Amgen, Biogen Idec, Boehringer, BMS, Celgene, EMD Serono, Janssen, MedImmune, Medac, Novartis, Novo- Nordisk, Pfizer, Roche, Sanofi Aventis, Servier, Takeda, and Vertex, Speakers bureau: AbbVie, Amgen, Biogen Idec, Boehringer, BMS, Celgene, EMD Serono, Janssen, MedImmune, Medac, Novartis, Novo- Nordisk, Pfizer, Roche, Sanofi Aventis, Servier, Takeda, and Vertex